Coral Fish Biodiversity Assessment on Different Locations (Case Study of the North Bali ICRG Area). - Potje, Emilian Ivarlyano; Wiyanto, Dwi Budi; Giri Putra, I Nyoman; Demianus Hukom, Frensly (Rekayasa, 2024)
Reef fish associated with artificial reefs are one indicator of success for artificial reef applications. This research was carried out in February 2023. Reef fish data was collected in three tidal conditions. Data of Coral fish was collected using the Underwater Visual Census (UVC) method. The data that collected includes abundance of species, individual abundance and fish size from 3 categories namely major, indicators and targets. From the results, the community structure at each location obtained the same diversity index and uniformity index which were classified as moderate to high and the dominance index was classified as low. For each tidal condition the diversity index obtained was classified as medium to high, the uniformity index is relatively high and the dominance index is low. The total abundance of species at each point ranges from 26 species represented by 13 families to 63 species represented by 19 families, and for each tidal condition it ranges from 11 species represented by 7 families to 42 species represented by 16 families. The total abundance of individuals at each point overall ranged from 1333-20,048 Ind/Ha, each tidal condition it ranges from 20- 980 individuals. The total biomass at each point overall ranged from 102,844- 1353,119 Kg/Ha, each tidal condition ranges from 2,154 to 63,780 kg. Based on the results, the species similarity index values at each point were categorized as medium, except for Les II and Galeri, which were classified as high, while the test results for each tidal condition ranged from medium to high at each point. Test results (Mann-Whitney) for each point based on individual abundance values and coral reef fish biomass generally showed significant differences except between the Gallery and Les II points, whereas for each tidal condition there were no significant differences. Based on the results of the Correspondence Analysis, it was found that there was a relationship between several types of fish with each research point and at each tidal condition, this shows that the artificial reef structure at each point and each tidal condition was successful in attracting fish populations.